The Role of miRNA Let-7a-1 and Let-7f-1 in Regulating Inflammatory and Angiogenic Pathways in Endometriosis - Saddang, Wahyuni; Abdullah, Nusratuddin; Hamid, Firdaus; Bte Ladju, Rusdiana; Idris, Irfan; Wahyuni, Sitti; Sriwijaya, Sriwijaya; Maidarti, Mila (Journal of Neonatal Surgery, 2025)
Background Endometriosis, a chronic gynecological disorder characterized by the ectopic growth of endometrial tissue, involves complex inflammatory and angiogenic mechanisms. MicroRNAs (miRNAs), particularly Let-7a-1 and Let-7f-1, have been identified as key regulators of these pathways, influencing the progression and symptoms of the disease. Objectives This review aims to explore the roles of miRNA Let-7a-1 and Let-7f-1 in the regulation of inflammatory and angiogenic pathways in endometriosis, highlighting their potential as biomarkers and therapeutic targets. Materials and Methods A comprehensive literature search was conducted using databases such as PubMed, Scopus, and Web of Science. Relevant studies published between 2000 and 2024 were included, focusing on the expression, function, and regulatory mechanisms of Let-7a-1 and Let-7f-1 in endometriosis. Key findings were synthesized to provide an updated understanding of their biological and clinical relevance. Results Evidence indicates that Let-7a-1 and Let-7f-1 play pivotal roles in modulating pro-inflammatory cytokines, angiogenic factors like VEGF, and cellular proliferation in endometriotic lesions. Dysregulated expression of these miRNAs is associated with enhanced inflammatory responses and aberrant angiogenesis, contributing to the persistence and progression of endometriosis. Furthermore, preclinical studies demonstrate that targeting Let-7 family miRNAs can mitigate these processes, suggesting their potential utility in therapeutic strategies. Conclusion Let-7a-1 and Let-7f-1 serve as critical modulators in the inflammatory and angiogenic pathways of endometriosis, offering insights into disease pathophysiology. Their roles as biomarkers and therapeutic targets warrant further investigation, paving the way for novel diagnostic and treatment approaches in endometriosis management.